Memanfaatkan Tumbuhan Sekitar Dalam Pelatihan Ecoprint Pada Siswa SD Negeri 062206 Kelurahan Tanah Seribu - Fatimah Zahra; Lisra Mahfirah; Nurul Ain Asnawati; Triana Triana; Ella Andhany (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
This ecoprint training activity aims to increase the knowledge, skills and understanding of fifth grade students at SD Negeri 026602, Tanah Seribu District, Binjai City, in utilizing natural materials in flowers or leaves that can produce colors. And also develop students' creativity so that they become creative and sensitive to the surrounding environment. This activity is carried out through the extension method, through 3 stages, namely: 1) Activity needs planning stage, 2) Implementation, and 3) Results presentation. Community service activities were implemented for 16 fifth grade students at SD Negeri 026602. The results of the Community Service activities were that the ecoprint training in Tanah Seribu sub-district, Binjai City went well. This is proven by the participation and enthusiasm of students at SD Negeri 026602, Tanah Seribu District, Binjai City. Researchers hope that knowledge from activities like this can be applied in life, giving rise to an entrepreneurial spirit from an early age.